Continuous electrooxdiation of sulfuric acid on boron-doped diamond electrodes - Hippauf, Felix; Doerfler, Susanne; Zedlitz, Ralf; Vater, Alfred; Kaskel, Stefan (Electrochimica Acta, 2014)
This study reports on the electrochemical oxidation of highly concentrated sulfuric acid by Diachem® boron-doped diamond electrodes. The scope of this work was to evaluate a proposed continuous electrooxidation process in order to prepare a resist removal bath that contains equivalent amounts of peroxosulfuric compounds as a common SPM (sulfuric acid and hydrogen peroxide mixture) bath. The electrochemical processes at the electrode surface were investigated by cyclic voltammetry and by titration of the reaction products under real working conditions (> 80 wt% H2SO4). Furthermore, an alternative electrolysis test cell setup, exhibiting a thin and mechanically stable ion exchange membrane will be used. For this process only one electrolyte circuit is performed. The initial electrolysis product H2S2O8 immediately undergoes hydrolysis and forms H2SO5. The obtained concentration of H2SO5 was similar to a reference SPM bath (> 0.14 mol l-1 H2SO5 in 90 wt% H2SO4), even though the current efficiency was lower than for more diluted solutions. This can be attributed to a complex interplay of side and consumption reactions of peroxosulfuric compounds. This electrolysis bath has the potential to be a very promising alternative to standard SPM baths, as it operates as a continuous and sustainable process.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Boron-doped diamond electrode; Electrooxdiation; Nafion; Peroxomonosulfuric acid; SPM bath